Intrinsic motivation and self-determination in exercise and sport - Chatzisarantis, Nikos L.D; Hagger, Martin (Human Kinetics, 2007)
The world of exercise and sport is fascinated by motivation and the factors that drive it. It's no wonder researchers both in and out of the sport domain will enthusiastically welcome Intrinsic Motivation and Self-Determination in Exercise and Sport. Motivation is central to many social psychological theories that aim to explain behavior, including self-determination theory, one of the most influential theories of human motivation developed in the last three decades. Intrinsic Motivation and Self-Determination in Exercise and Sport examines the contribution of this theory to the understanding of motivation and behavior in the domains of exercise and sport. This is the first book to synthesize key research of self-determination theory as it relates to sport and exercise into one convenient volume. Written by a broad range of leading researchers, this reference will be a trend setter in the understanding of internal motivation and how to maximize performance and adherence. Furthermore, this volume will fill in research gaps, improve existing research, and set new directions for research in this vibrant area. Self-determination theory is based on the premise that individuals pursue self-determined goals to satisfy their basic psychological needs to independently solve problems, interact socially, and master tasks. The book begins with an introductory chapter in which the founding fathers of self-determination theory, Edward L. Deci and Richard Ryan, provide an overview of the theory and its constituent subtheories and chart its history with respect to exercise and sport, highlighting classic studies and seminal works along the way. This introduction masterfully provides sufficient theoretical grounding and serves as an excellent prologue to subsequent chapters